2015
DOI: 10.31795/baunsobed.645355
|View full text |Cite
|
Sign up to set email alerts
|

Turi̇zm Ve Mutluluk Arasindaki̇ İli̇şki̇ Üzeri̇ne Kavramsal Bi̇r Değerlendi̇rme

Abstract: Öz: Günümüzde yaşam koşullarının ağırlaşması, yaşanan ekonomik krizler ve yoğun iş temposu gibi faktörlerin artması, mutluluk kavramına duyulan ihtiyacı da gündeme getirmektedir. Nitekim bu araştırmada; mutluluk kavramı, güncel ve gelişime açık bir konu olması sebebiyle tercih edilmiştir. Bireylerin mutluluğunu yaşam koşulları %10, genetik özellikleri %50 ve amaçlı etkinlikler ise %40 oranında etkilemektedir. Amaçlı etkinlikler kapsamında mutlu olmaya yönelik doğrudan yapılan faaliyetler ele alınmaktadır. Bire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…For this reason, the research examined the relationships between recreational activities and happiness, life satisfaction and life satisfaction. In the studies examined, in parallel with the increase in the level of participation in recreational activities, happiness (Demirbulat & Avcıkurt, 2015;Güven & Yavuz, 2018), happiness and quality of life (Demirbaş, 2020;Ortaç, 2019), quality of life (Ellis, Compton, Tyson & Bohlig, 2002;Salihoğlu, 2016;Silverstein & Parker, 2002) found that quality of life and life satisfaction (Eime et al, 2010) were positively affected.…”
Section: The Relationship Between Recreation and Subjective Well-beingmentioning
confidence: 99%
“…For this reason, the research examined the relationships between recreational activities and happiness, life satisfaction and life satisfaction. In the studies examined, in parallel with the increase in the level of participation in recreational activities, happiness (Demirbulat & Avcıkurt, 2015;Güven & Yavuz, 2018), happiness and quality of life (Demirbaş, 2020;Ortaç, 2019), quality of life (Ellis, Compton, Tyson & Bohlig, 2002;Salihoğlu, 2016;Silverstein & Parker, 2002) found that quality of life and life satisfaction (Eime et al, 2010) were positively affected.…”
Section: The Relationship Between Recreation and Subjective Well-beingmentioning
confidence: 99%
“…less, their happiness is ensured (Işık et al, 2017). At the same time, individuals' satisfaction with their health, business, or marital life is one of the indicators of happiness (Demirbulat and Avcıkurt, 2015).…”
Section: The Concept Of Happinessmentioning
confidence: 99%
“…Alanyazında Oxford Mutluluk Ölçeğinin kullanıldığı (Göl 2008;Kara 2010;Tekirgöl 2011;Demirbulat ve Avcıkurt 2015) birçok çalışma bulunmaktadır. Tekirgöl (2011) tarafından "Çalışanlarda Mesleki Benlik Saygısının İş Tatmini ve Yaşam Mutluluğu ile İlişkisi" adlı yüksek lisans tezinde Oxford Mutluluk Ölçeğinin güvenilirliği test edilmiş ve Cronbach alfa değeri %86,3 bulunmuştur.…”
Section: Geçerlilik Ve Güvenirlilik Analiziunclassified